Da di zhen yu Ming Qing Shanxi xiang cun she hui bian qian - Hao, Ping, 1968- (Beijing Shi : Ren min chu ban she, 2014)
Summary in vernacular field only.
Includes bibliographical references.
Keywords: Earthquakes -- China -- Shanxi Sheng -- History; Earthquake relief -- China -- Shanxi Sheng -- History; Shanxi Sheng (China) -- Social conditions; China -- Social conditions -- 960-1644.; China -- Social conditions -- 1644-1912.